Exploring English teachers’ barriers in integrating moderation values amid curriculum changes - Giyoto Giyoto; Mokh. Yahya; Elen Inderasari; Purwanto Purwanto; Baidi Baidi (English Language Teaching Educational Journal, 2026)
The moderation value integration is sensitive for religion-based educational institutions, mainly for madrasahs, in Surakarta in preventing the social conflicts among different ethnics, races, and religions. The last five-times changes of the national curriculum at high schools, since 2004, have brought about schools and teachers’ barriers in integrating the moderation values to their English teaching and learning process. This paper explores the English teachers’ barriers in integrating the moderation values in their teaching and learning activities amid the curriculum changes. The data were taken qualitatively using interviews and observations to English teachers and headmasters of the two best madrasahs, MAN 1 and MAN 2, in Surakarta. The triangulated data were analyzed using Analytic Induction into eight kinds of teachers’ barriers. The findings show that the teachers have four areas of barriers: a) low moderation value literacy and no manuals; b) past failure experiences; c) moderation integration as a new habit; d) learning English and moderation value achievement imbalances. They have no barrier in four areas:  a) the expertise shift; b) the school power relations; c) the interpersonal relationships; d) the human resource replacement. This research helps the schools and teachers in identifying and solving the eight areas of barriers in implementing new change of curriculum, mainly in integrating the moderation values. These findings imply that school and teachers’ readiness and creativity are basic in integrating moderation values amid the curriculum changes.